Façade design modification in complying the Indonesia's national standard of energy conservation for tall building envelope – Case study: Green Office Park 9, Serpong, Indonesia. Issue 1 (September 2021) - Hajji, A M; Hilmi, A R. Z.
Abstract: Most tall buildings use glass as its façade and exterior materials, which makes the building's envelope is exposed to heat penetration. It is important to select and design the proportion between transparent and opaque materials for building façade to reduce the heat gain from outside, which is strategic to conserve the energy use for tall buildings. This study is aimed to observe the use of building façade materials in accordance with the strategic effort to reduce the heat gain in order to conserve the energy for AC system. The façade design modification is calculated by using Overall Thermal Transfer Value (OTTV) method in compliance with the Indonesia's National Standard of Energy Conservation for Tall Buildings. The results show that the modification on façade design can reduce the heat gain and improve thermal performance of the building. There is a dramatic change of OTTV from 124.40 w/m 2 on original design to 27.73 w/m 2 after several steps of façade modification. The biggest reductions of OTTV is obtained when modifications on openings are applied. Since the heat transmission is mainly coming into buildings through openings, modifications on glass and windows are the keys. The change of glass material, from clear-glass to those with lower shading coefficient (SC) gives reduction of 37.52 w/m 2 .